Development of SNAP-tag-based fusion proteins targeting HIV-1 viral reservoirs - Cingo, Siphelele Sanele (Division of Chemical and Systems Biology, 2021)
Background Globally, the HIV/AIDS epidemic has cost over 35 million lives and approximately a further 37 million people are currently infected with HIV. In South Africa alone, more than 7 million people are HIV positive. Since the initiation of combination antiretroviral therapy (cART), viral replication can be supressed below the limit of detection by conventional testing. There is, however, no approved therapy for the cure of HIV. This is because HIV establishes viral reservoirs in memory CD4+ T-cells, where replication is low or arrested, allowing prolonged survival. Since there is little or no replication, a therapeutic strategy which targets the viral production and replication becomes ineffective and upon cessation of antiretroviral therapy a dramatic viral relapse occurs. The eradication of HIV, therefore, requires the targeted killing of the reservoir cells, or latency reversal followed by the prevention of further infection using cART. Targeting of cell-surface antigens for therapeutic purposes is the basis of immunotherapy. FDA-approved monoclonal antibodies such as Trastuzumab have been used to treat breast cancer via the human epidermal growth factor 2 (HER2) receptor. Immunotoxins (ITs) composed of an antibody fragment fused to apoptosis-inducing protein toxins targeting cellsurface antigens have been used for therapy of refractory leukaemia. The anti-CD22 recombinant IT Moxetumomab pasudotox based on Pseudomonas aeruginosa exotoxin A (ETA) has been FDA approved to treat hairy cell leukaemia. Moxetumomab pasudotox targets the antigen CD22 found on the surface of tumour cells. The HIV neutralizing VHH-nanobody J3, isolated from an immunised Llama has demonstrated anti-HIV properties against more than 95 % of HIV strains in vitro. As part of an ongoing project to develop a J3-ETA IT, this work sought to produce a J3-SNAP fusion protein by osmotic stress expression in the presence of compatible solutes in the periplasmic space of E. coli. SNAP-tag is a self-labelling protein that covalently binds benzylguanine (BG)-modified substrates in a 1:1 stoichiometric ratio. When recombinantly fused to any protein of interest, SNAP-tag allows the stable labelling of the protein of interest of in vitro and in vivo imaging. The periplasmic space of bacteria has been reported as a dedicated compartment to express functional proteins of interest. Furthermore, osmotic stress expression in the presence of compatible solutes has been reported to result in up to a thousand-fold increase in protein yield for difficult to express proteins. This study ultimately aimed to understand whether a functional J3-SNAP or J3-ETA can be expressed under osmotic stress in the presence of compatible solutes, in the periplasmic space of E. coli. 11 Experimental work In this study, a SNAP-tag-based fusion protein and an ETA-based IT were designed using J3, an anti-HIV-1 Env VHH-nanobody isolated from an immunised llama. Using the SnapGene® software (v.5.0.8, GSL Biotech LLC, USA), in silico design and cloning of an ETA-based IT J3-ETA and SNAP-tag-based fusion protein J3-SNAP was performed. Molecular cloning of designed open reading frames (ORFs) was performed into appropriate bacterial expression plasmid vectors. Plasmid vectors confirmed to contain the required ORFs by Sanger sequencing were transformed into E. coli BL21-DE3. Histidine-tagged J3-SNAP was expressed by osmotic stress in the presence of compatible solutes. J3-SNAP was purified by IMAC and assessed by SDS-PAGE and Western blot analysis. To ascertain the binding of J3- SNAP to cells expressing HIV-1 Env in vitro, recombinant Env protein was transiently transfected into HEK293T-cells to generate an Env expressing cell line. Cell-surface binding of SNAP-Surface® Alexa Fluor® 488 -conjugated J3-SNAP on Env expressing HEK293Tcells was assessed by confocal microscopy analysis. Results Successful expression of J3-SNAP in E. coli BL21-DE3 was confirmed by SDS-PAGE and Western blot analysis. The J3-SNAP fusion protein was subsequently purified by IMAC. Purified J3-SNAP was conjugated to the benzyl guanine-modified fluorophore SNAPSurface® Alexa Fluor® 488 and full-length conjugated protein was confirmed by combinations of SDS-PAGE and Western blot analysis. Cell-surface binding of J3-SNAP to HIV-1 Env-expressing HEK293T-cells was demonstrated in vitro by confocal microscopy analysis. These results prompted the generation of the IT, J3-ETA, by replacing SNAP-tag with ETA. Conclusion Successful binding studies suggest using J3 to target HIV-1 Env. Accessing patient probes would allow for the confirmation of these results for future human applications. Future in vitro studies would need to confirm the selective elimination of Env expressing T-cells by J3-ETA and thereafter confirmed on Env-positive patient probes.